Penguatan Pendidikan Karakter Berbasis Pancasila melalui Kurikulum K13 di Sekolah Dasar - Ika Lis Mariatun; Dian Eka Indriani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2018)
This research is a descriptive qualitative research using triangulation by using datacollection technique, that is questionnaire / questionnaire, observation, and interview.the research was conducted at elementary school in Kamal sub-district usingcurriculum 2013; there are five elementary schools in Kamal namely SDN Banyuajuh2, SDN Banyuajuh 3, SDN Banyuajuh 6, SDN Kamal 1, SDN Gili Anyar. The resultsof this study are expected to examine much more in the development of characterformation of the Nation that is character that contains the value of Pancasila becauseeducation that contains Pancasila values with the essence of Pancasila as the nation'slife view is the main shield to face the challenges and threats as the nation's characterformers which is a unique thing and distinctive that became the distinguishing elementbetween one nation and another nation.